Programmed death‐1 blockade for multiple basal cell carcinomas: clearing the field systemically?. (1st September 2018) - Haug, V.; Schilling, B.
Abstract: Linked Article: Moreira et al. Br J Dermatol 2018; 179 :747–749 .